High Performance Liquid Chromatographic Method for Estimation of Repaglinide in Tablet Dosage Forms - MEETA A. JILADIA; S. S. PANDYA; ASHOK G. JILADIA (International Journal of Pharma and Bio Sciences, 2010)
A simple and sensitive, HPLC method has been developed and validated for the quantitative estimation of repaglinide in its single component tablet formulations (2 mg). Determination was performed using a Thermo BDS C18 column with mobile phase phosphate buffer: acetonitrile (pH 6.0; 45:55, v/v), and ultraviolet (UV) detection at 288 nm. The method was validated in terms of linearity (10–60 µg/ml), precision (intra-day variation below 0.6, inter-day variation below 0.2), accuracy (97.9 to 100.1%), ruggedness (within 0.5%) and specificity. The limit of detection and limit of quantification for repaglinide were found to be 1 µg/ml and 3 µg/ml, respectively. The developed method was successfully used for the assay of repaglinide tablet formulations. The method is simple, sensitive and precise; it can be used for the routine quality control testing of marketed formulations.